Evaluation of the physical and chemical quality of the soil in different land uses, Frutal, MG - Galati, Pedro Canassa; Mata , Jhansley Ferreira da; Korasaki, Vanesca; Negrão, José Neto Vieira; Martins, Heytor Lemos; Mendes, Gabriel Gomes; Vieira, Lelisberto Baldo; Alves, Pedro Luís da Costa Aguiar (Seven Editora, 2024)
Soils in areas of agricultural production, in the Cerrado region, when under intense cultivation, can present alterations in the chemical and physical constitution. This work aimed to evaluate the physical and chemical quality of the soil, at different depths in different land use systems (SUT): sorghum, rubber tree, pasture and native Cerrado in the municipality of Frutal-MG. In each SUT area, three samples were collected, at two depths. The design used was completely randomized 4x2, with four cropping systems and two depths, in three areas with the same SUT. The native forest system at a depth of 20-40 cm showed better values for electrical conductivity. For soil moisture the depth 0-20 cm were higher in the pasture, native forest and rubber tree systems, and 20-40 cm was native forest, between the depths the pasture system was greater in 0-20 cm. SUTs pasture showed higher soil density at depth 0-20 cm within and between depths. In the chemical analysis of the soil, regardless of the depth, the native forest has higher acidity. The copper content in the 20-40 cm depth, within the SUTs and depths, is higher for pasture, native forest, and rubber trees. In the sum of the bases within the 0-20 cm depth, the SUTs with the highest value were pasture, native forest and sorghum. DOI:https://doi.org/10.56238/sevened2023.001-005